In vitro efficacy of organic amendments and biocontrol agents against Sclerotium rolfsii causing groundnut stem rot disease - Deepika, B; Sheela, J; Indra, N; Kalaiyarasi, R; Navamaniraj, K N (Plant Science Today, 2025)
Groundnut is a crucial oil seed crop cultivated worldwide and often referred to as the "King of Oil Seeds." However, its productivity is significantly reduced by various biotic and abiotic stresses. Among these, soil-borne fungal infections, particularly stem rot disease caused by Sclerotium rolfsii Sacc., pose a major threat, potentially leading to yield losses of up to 80 percent. In this study, stem rot-infected samples were collected from five major groundnut-growing districts in Tamil Nadu, India, and nine isolates of S. rolfsii were obtained. Based on pathogenicity tests, the most virulent isolate was identified and characterized at the molecular level. The pathogen produces a resting structure called sclerotia, which survives in soil for many years. Considering the ill effects of chemical methods of management, the present study is focused on non-chemical methods using organic amendments and biocontrol agents against the pathogen. Six amendments, viz., groundnut cake, neem cake, castor cake, cotton cake, sesame cake, and cow manure, were tested against S. rolfsii under in vitro conditions at two concentrations (5 % and 10 %). Among these, sesame cake exhibited the highest inhibition of 48.36 percent and 63.80 percent at 5 percent and 10 percent concentrations, respectively. Through GC-MS analysis, the bioactive compounds, viz., 9,12-Octadecadienoic acid (Z, Z) - (100%) and 9-Octadecenoic acid (E) - (76.13%), responsible for pathogen inhibition were identified. Furthermore, rhizospheric bacterial biocontrol agents were evaluated against S. rolfsii, which revealed that isolate B2 showed maximum inhibition (79.48%). The bacterial isolate B2 was molecularly characterized and confirmed as Bacillus subtilis (PP882830).